2021
DOI: 10.3390/cancers13092184
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer–Dendritic Cell Interactions in Liver Cancer: Implications for Immunotherapy

Abstract: Natural killer (NK) and dendritic cells (DCs) are innate immune cells that play a crucial role in anti-tumor immunity. NK cells kill tumor cells through direct cytotoxicity and cytokine secretion. DCs are needed for the activation of adaptive immune responses against tumor cells. Both NK cells and DCs are subdivided in several subsets endowed with specialized effector functions. Crosstalk between NK cells and DCs leads to the reciprocal control of their activation and polarization of immune responses. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 214 publications
(271 reference statements)
0
14
0
Order By: Relevance
“…NK cells also interact with DCs, through cell-to-cell contact and soluble mechanisms, recently reviewed elsewhere ( 13 ). As for NK cell-monocyte crosstalk, also in the case of NK cells and DCs exists a bidirectional interaction, responsible on one hand for reciprocal cell activation, on the other hand for homeostatic control aimed at preventing excessive immune activation.…”
Section: Nk Cell Crosstalk With Other Immune Cells In Sars-cov-2 Infe...mentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells also interact with DCs, through cell-to-cell contact and soluble mechanisms, recently reviewed elsewhere ( 13 ). As for NK cell-monocyte crosstalk, also in the case of NK cells and DCs exists a bidirectional interaction, responsible on one hand for reciprocal cell activation, on the other hand for homeostatic control aimed at preventing excessive immune activation.…”
Section: Nk Cell Crosstalk With Other Immune Cells In Sars-cov-2 Infe...mentioning
confidence: 99%
“…NKp46 and NKp30 are expressed on virtually all resting NK cells, whereas NKp44 expression is acquired upon NK cell activation. These molecules are important for inducing NK cell cytotoxic function against target stressed-cells and in the crosstalk with other cell types, such as dendritic cells (DCs) ( 13 ). Other important activating NK receptors are the C-type lectin-like receptors NKG2D and NKG2C and the activating Killer Immunoglobulin-Like Receptors (KIRs).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that PDSS1 in HCC was negatively related to dendritic cells (DCs, pDCs), cytotoxic cells, and CD8 T cells. DCs are a type of antigen-presenting cell which have an important regulatory effect on tumor immune response, and can positively regulate the immune response to HCC ( 31 , 32 ). In addition, CD8 + T cells can secrete cytotoxic particles, making them a type of cytotoxic cell that plays an important role in antitumor immunity ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tumor-cell material is released that can be processed by further DCs and be presented to T cells [39]. As activation of NK cells is mediated by IL-12 and type I interferons [40], BDCs activated with R848 + poly(I:C) demonstrated potent NK-cell activation with respect to CD69 expression and IFN-γ secretion. Importantly, NK-cell activation has been shown to correlate with clinical outcomes in several clinical trials, including those of a DC vaccine targeting WT1 in AML [39,41,42].…”
Section: Discussionmentioning
confidence: 99%